Topónimos y cronología: notas sobre una puerta distinta al estudio del pasado - Mentz, Brígida von (El Colegio de México, A.C., 2017)
This article is an invitation for historians to consider the importance of linguistic history and engage in a dialogue with others who study Mexico’s ancient past from other disciplines. Using European and Mexican examples, it argues for the utility of studying place-names when examining the past of different societies. It then analyzes indigenous toponyms in Mesoamerica, proposing that they could be a key to shedding light on remote epochs. Through the analysis of more than 4,000 indigenous toponyms, their connection to certain languages and, in some cases, their grammatical structure, it puts forward a chronology for epochs for which we lack written records.